If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -1 + 5y = 65y + -36 Reorder the terms: -1 + 11y + 5y = 65y + -36 Combine like terms: 11y + 5y = 16y -1 + 16y = 65y + -36 Reorder the terms: -1 + 16y = -36 + 65y Solving -1 + 16y = -36 + 65y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-65y' to each side of the equation. -1 + 16y + -65y = -36 + 65y + -65y Combine like terms: 16y + -65y = -49y -1 + -49y = -36 + 65y + -65y Combine like terms: 65y + -65y = 0 -1 + -49y = -36 + 0 -1 + -49y = -36 Add '1' to each side of the equation. -1 + 1 + -49y = -36 + 1 Combine like terms: -1 + 1 = 0 0 + -49y = -36 + 1 -49y = -36 + 1 Combine like terms: -36 + 1 = -35 -49y = -35 Divide each side by '-49'. y = 0.7142857143 Simplifying y = 0.7142857143
| 4(9p+4q)= | | 7+10v-7v-7= | | -1/x-2=0 | | 5x+5x+4+9=6x+4+3x | | 242=169+13c | | -131=3(3-6n)-2n | | ((7y+9)/6)+((y-6)/3)=4 | | 5x^(2/3)-44x^(1/3)-9 | | h-0.78=2.65 | | (4u-3)/5=4-((7u-2)/4) | | 4x+2x-x+3x= | | (7-3)2+3(8)= | | (4f+13g)(2w)= | | 7/2x-5=4/x+1 | | (4v-4)/3=((v+1)/6)+2 | | =x^2+22x+72 | | 11+21(11)=(13+c)13 | | 12y-10=-11+9y | | 3(x-6)/4=4x+6 | | 3(2n+1)+4(n-2)= | | h/2+7=10 | | 1=n/4-1 | | 20=5x+7x^2 | | 14=9-p | | 2+x/5=0 | | 4+b/-2=-2 | | 0=14d+8d^2 | | (6+y)(2y+5)=0 | | 12x+15=5x+62 | | 5x+x-4=-4 | | 2/3x-1/2y=12 | | (6x-4)-(2x+5)= |